Energy Use Greenization, Carbon Dioxide Emissions, and Economic Growth: An Empirical Analysis Based in China - Xinmin, Wang; Iqbal, Kashif; Wang, Yichu (Frontiers in Environmental Science, 2022)
Developing countries are constantly facing the problem of environmental degradation. Environmental degradation is caused by the consumption of non-renewable energy for economic growth, but the consequences of environmental degradation cannot be ignored. The main purpose of this study is to investigate the relationship between three variables (i.e., energy use greenization, CO2 emission, and economic growth) in the case of China using simultaneous equation modeling techniques and data for the period 2000–2018. The results indicate that (1) there is a long-term equilibrium relationship between energy use greenization, carbon emissions, and economic growth in China. Energy use greenization not only reduces carbon dioxide emissions but also promotes sustainable economic growth in China. (2) Carbon emissions and economic growth have promoted energy use greenization, indicating that the pressures of environmental climate and economic transformation in China have forced energy use greenization to a certain extent. (3) The contribution rate of energy use greenization to economic growth shows an inverted U-shaped trend that rises first and then decreases subsequently, while carbon emissions have a relatively large contribution rate to green energy use and economic growth. These results have far-reaching policy directions for the environmental sustainability goals of the Chinese economy.